Ramón García de Haro, Karl Marx: El Capital, Colección "Crítica Filosófica", E. P. E. S. A., Madrid, 1977, 222 pp. - Derisi, Octavio Nicolás (1977)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina